Prototype of Laboratory-Scale Thin Film Deposition System Based on Plasma Arc with Process Parameter Optimization - Yuniarto Agus Winoko; Akbar Andika Marta; Agus Dani (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
In this modern era, technological developments are growing so fast, from information technology, communication technology, transportation, medical to industrial technology. One of the advances in the rapidly developing industrial world is the technique of coating metal or material surfaces. There are many methods of material surface coating techniques such as Physical Vapor Deposition (PVD), implantation, radio frequency (RF) sputtering, chemical vapor deposition, polymer supported electrodes (PSE), and electrochemical deposition. The Electrochemical Deposition method is a simple method with cost advantages, but this method requires processing of liquid waste which has recently become a public concern regarding environmental pollution. The APD (Arc Plasma Deposition) method has a higher level of satisfaction in fulfilling the requirements for deposition of a material, namely it is easy to control the size of the particles to be deposited and is faster in the deposition process and also has a very small impact on environmental pollution. This method requires quite large assets for its application so not many people know the stages of layer deposition. Therefore, the preparation of a prototype of a laboratory scale thin film growth machine was carried out and can carry out the deposition of a material onto a material. To optimize the layer growth results, adjustments are required in the machine parameter settings and the pure gas rate used